2021
DOI: 10.1007/s00216-021-03486-2
|View full text |Cite
|
Sign up to set email alerts
|

Development of a method for assessing the accumulation and metabolization of antidepressant drugs in zebrafish (Danio rerio) eleutheroembryos

Abstract: Antidepressant drugs are widely used for the treatment of common mental or other psychiatric disorders such as depression, which affect about 121 million people worldwide. This widespread use has contributed to the input of these pharmaceuticals and their metabolites into the environment. The aim of this work was to develop an analytical method to quantify the most widely used antidepressant drugs, selective serotonin reuptake inhibitors (SSRI), and their main metabolites in the environment. For this, a new an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…In this sense, an alternative method based on the OECD 305 assay, developed in a research group using zebrafish eleutheroembryos (Danio rerio; Sanz-Landaluze et al, 2015) for bioaccumulation studies, is used in the present study, drastically reducing the time, cost, and animal suffering. In addition, in our recent studies (Molina-Fernández et al, 2021) it has been observed that eleutheroembryos are able to biotransform the parental compounds into some of their metabolites during the exposure time with this alternative method. This has opened up the possibility for us to continue using it for metabolic studies because this is an underdeveloped field with no official testing or regulation.…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, an alternative method based on the OECD 305 assay, developed in a research group using zebrafish eleutheroembryos (Danio rerio; Sanz-Landaluze et al, 2015) for bioaccumulation studies, is used in the present study, drastically reducing the time, cost, and animal suffering. In addition, in our recent studies (Molina-Fernández et al, 2021) it has been observed that eleutheroembryos are able to biotransform the parental compounds into some of their metabolites during the exposure time with this alternative method. This has opened up the possibility for us to continue using it for metabolic studies because this is an underdeveloped field with no official testing or regulation.…”
Section: Introductionmentioning
confidence: 99%
“…To assess the risk to human health and the environment, the European Registration of Chemicals Regulation (REACH) classifies chemicals according to persistence, bioaccumulation, and toxicity studies during their entire life cycle, including transformation processes in the environment and metabolization. There is evidence that the bioactive metabolites [3,4] can change the bioaccumulation and overall toxicity of the parent pollutants they come from [5][6][7]. In this context, analytical chemistry has become an essential part of the strategy to understand the ecotoxicity of POPs [8], through the determination of metabolites to elucidate metabolic pathways and their concentration to assess real exposure levels [7].…”
Section: Introductionmentioning
confidence: 99%
“…For example, El-Amrani et al ( 2012 ) proposed a protocol to evaluate the bioconcentration of three pesticides, with different chemical and toxicological characteristics (chlorpyrifos, atrazine, and dicofol), in zebrafish eleutheroembryos (from 72 to 120 hpf). Molina-Fernández et al ( 2021 ) developed a miniaturized protocol that used zebrafish eleutheroembryos (from 72 to 120 hpf) to evaluate the bioconcentration, biotransformation of selective serotonin reuptake inhibitors (fluoxetine, sertraline, paroxetine, and citalopram), and their main metabolites (norfluoxetine, norsetraline, and desmethylcitalopram). Massei et al ( 2021 ) investigated the effects of 3 narcosis‐inducing chemicals (phenanthrene, 1,3,5-trichlorobenzene, and pentachlorobenzene) on the respiration of zebrafish eleutheroembryos in a short exposure window (from 58 to 72 hpf) to avoid effects on growth that would influence respiration.…”
Section: Introductionmentioning
confidence: 99%